1991
DOI: 10.1111/j.1365-2885.1991.tb00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of ticarcillin and clavulanate in foals after intravenous and intramuscular administration

Abstract: The pharmacokinetics and bioavailability of ticarcillin and clavulanate were determined after intravenous (i.v.) or intramuscular (i.m.) administration of ticarcillin disodium (50 mg/kg) combined with clavulanate potassium (1.67 mg/kg) to groups of healthy foals at 3 days and 28 days of age. After i.v. administration of the combination to five foals, the disposition kinetics of ticarcillin and clavulanate were best described using a two-compartment open model. Mean plasma elimination-rate constant (beta) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
5
29
0
Order By: Relevance
“…The time to reach peak concentration (tmax) reflects the rate of absorption, whereas the peak concentration (Cmax) is affected by the rate and extent of absorption. A peak plasma concentration of 10.71 mg/1 of amoxicillin was reached at 1.93 h (tmax-tlag) and of 5.75 mg/1 of clavulanic acid at 1.60 h. The tmax values obtained in the present study indicates rapid absorption and is similar to the value reported for amoxicillin in mares of 1.5 h but the mean peak concentration was lower (2.73 mg/I) (30). Such poor absorption and the low peak plasma concentration of amoxicillin in goats were in contrast to the results of studies with dogs and humans (12,13).…”
Section: Oral Administrationsupporting
confidence: 77%
See 2 more Smart Citations
“…The time to reach peak concentration (tmax) reflects the rate of absorption, whereas the peak concentration (Cmax) is affected by the rate and extent of absorption. A peak plasma concentration of 10.71 mg/1 of amoxicillin was reached at 1.93 h (tmax-tlag) and of 5.75 mg/1 of clavulanic acid at 1.60 h. The tmax values obtained in the present study indicates rapid absorption and is similar to the value reported for amoxicillin in mares of 1.5 h but the mean peak concentration was lower (2.73 mg/I) (30). Such poor absorption and the low peak plasma concentration of amoxicillin in goats were in contrast to the results of studies with dogs and humans (12,13).…”
Section: Oral Administrationsupporting
confidence: 77%
“…In sheep, however, the bioavailability of ampicillin after oral administration is much lower, namely 6.94% (2). In the present study, the biovavailability of amoxicillin was 27%, similar to the data reported for pre-ruminant veal calves (29% and 32% when given with and without milk, respectively) (35), but higher than those reported for starved horses (5%) (9) and mares (10.46%) (30). No data on the oral bioavailability of clavulanic acid in domestic animals are available.…”
Section: Oral Administrationsupporting
confidence: 72%
See 1 more Smart Citation
“…Since then AMX disposition was studied after its administration by different routes in production animals (Archimbault et al, 1981;, Nouws et al, 1986, Wilson et al, 1988. According to Erskine et al (2002) We performed some studies with the objective of evaluating the PK behavior of AMX trihydrate in serum and milk after its IM administration at therapeutic dose in healthy lactating cows (Mestorino et al, 1997) (Fig.…”
Section: Amoxicillinmentioning
confidence: 99%
“…The pharmacokinetics of amoxicillin in the chicken followed a two-compartment open model in view of the bi-exponential decline of plasma amoxicillin concentrations; this kinetic disposition was similar to that described previously in man, cows, mares, horses, dogs, and sheep and goats. [13][14][15][16][17][18] Following intravenous administration, the disappearance of the drug from the plasma of chickens was characterized by an initial rapid distribution phase (t0.5α) 0.22 h for both groups; followed by a slower elimination phase (t0.5β) 8.05 and 6.71 h for both groups, respectively. The results indicate that amoxicillin distributed more quickly after intravenous dosing.…”
Section: Discussionmentioning
confidence: 99%